PERBEDAAN PENGARUH LATIHAN ZIG-ZAG DAN LATIHAN SEGITIGA TERHADAP KEMAMPUAN DRIBBLE BOLA DALAM PERMAINAN SEPAK BOLA PADA ATLET USIA 10-12 TAHUN SEKOLAH SEPAK BOLA (SSB) AKADEMI PLUMPUNGAN UNITED - Kurnia Surya Utama; Agustanico Dwi Muryadi; Karlina Dwijayanti (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
This study aims to determine the difference in influence between zig-zag dribble training and triangle dribble training on the ability to dribble the ball in soccer games in athletes aged 10-12 years at SSB Plumpungan United Academy. The method used is an experiment with a pretest-post-test design. The population of this study was 50 athletes aged 10-12 years at SSB Plumpungan United Academy. The sample used in this research was 30 people using random sampling technique through lottery. Of the 30 students used as research samples, they were divided into two groups using ordinal pairing. Group 1, consisting of 15 people, received zig-zag dribble training. Group 2, consisting of 15 people, received triangle dribble training. Data collection techniques using tests and measurements of soccer dribbling abilities. Data analysis technique with t-test with a significance level of 5%. The research results showed that there was a significant difference in the influence between zig-zag dribble training and triangle dribble training on the ability to dribble the ball in soccer games in athletes aged 10-12 years at SSB Plumpungan United Academy with a calculated t-test value of 6.99 and a t-table of 2.14 level. significance 5%. From the results of calculating the percentage increase in ball dribbling ability, it is known that group 1 had an increase of 20.24%, while group 2 was 6.43%.